Policy expertise in contemporary democracies - Brooks, Stephen; Stasiak, Dorota; Żyro, Tomasz (Ashgate, 2012)
The contributors to this insightful and original volume argue that across the western world in general, the political expert occupies as important a role today as at any time in the past.